2000
DOI: 10.1007/s004110000069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium (K) supply on the uptake of 137 Cs by spring wheat ( Triticum aestivum cv. Tonic): a lysimeter study

Abstract: A lysimeter experiment was carried out on a relatively infertile soil to examine the effect of potassium fertiliser application on the uptake of radiocaesium by spring wheat. Porous ceramic cups were used to obtain samples of soil solution. Results showed that the uptake of radiocaesium by spring wheat was reduced by the addition of potassium. However this inhibitory effect was less marked at later stages of plant growth due to factors such as the spatial variability of potassium within the soil, differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
5
15
0
Order By: Relevance
“…Thus, one mechanism whereby increasing rhizosphere K protects plants from Cs in the environment is by reducing their Cs uptake. This observation is consistent with previous studies showing that increasing rhizosphere K reduces Cs uptake (Sutcliffe, 1957;Bange and Overstreet, 1960;Handley and Overstreet, 1961) and accumulation (Menzel, 1954;Cline and Hungate, 1960;Nishita et al, 1960Nishita et al, , 1962Jackson et al, 1965;Jackson and Nisbet, 1990;Shaw and Bell, 1991;Shaw et al, 1992;Belli et al, 1995;Smolders et al, 1996aSmolders et al, , 1996bZhu et al, 1999) by plants and provides a rationale for using K fertilization as a countermeasure in radiocesiumcontaminated soils (Konoplev et al, 1993;Prister et al, 1993;Zhu et al, 2000;. It was also observed that increasing [K] agar in the presence of Cs also increased [K] shoot (Fig.…”
supporting
confidence: 82%
“…Thus, one mechanism whereby increasing rhizosphere K protects plants from Cs in the environment is by reducing their Cs uptake. This observation is consistent with previous studies showing that increasing rhizosphere K reduces Cs uptake (Sutcliffe, 1957;Bange and Overstreet, 1960;Handley and Overstreet, 1961) and accumulation (Menzel, 1954;Cline and Hungate, 1960;Nishita et al, 1960Nishita et al, , 1962Jackson et al, 1965;Jackson and Nisbet, 1990;Shaw and Bell, 1991;Shaw et al, 1992;Belli et al, 1995;Smolders et al, 1996aSmolders et al, , 1996bZhu et al, 1999) by plants and provides a rationale for using K fertilization as a countermeasure in radiocesiumcontaminated soils (Konoplev et al, 1993;Prister et al, 1993;Zhu et al, 2000;. It was also observed that increasing [K] agar in the presence of Cs also increased [K] shoot (Fig.…”
supporting
confidence: 82%
“…This suggests that uptake of 137Cs from soil is regulated more by internal K content than the 137Cs/K ratio in soil, as much recent literature indicates (e.g., Zhu et al, 2000).…”
Section: Experiments 6: Spatial Distribution Of Applied Potassium and supporting
confidence: 64%
“…In a more recent study (Zhu et al, 2000), week-old wheat seedlings were grown for three days in nutrient cultures with or without added K. When subsequently exposed to test solutions containing Cs, the previously K-starved seedlings absorbed 137 Cs far more rapidly than the unstarved seedlings, with a linear range in solution concentration from 700 to 6500 Bq L -1 . Such uptake was greatly lessened as K in the test solutions increased from 2 to 12 mg L -1 (~ 50 to 300 µM).…”
Section: Summary Discussionmentioning
confidence: 99%
“…Radiocesium is readily transferred along the food chain and may pose a long-term radiation risk to humans. Potassium (K), which is chemically similar to cesium (Cs), influences Cs dynamics in soil, and radiocesium uptake by plants is strongly dependent on K concentration (Zhu 2001). As an agricultural countermeasure to reduce radiocesium uptake by rice or upland crops, K fertilization is an effective and practical method for several soil types.…”
Section: Introductionmentioning
confidence: 99%